1984
DOI: 10.1007/bf00504983
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alpha-adrenoceptor agonists and antagonists in a maze-exploration model of ?fear?-motivated behaviour

Abstract: An elevated X-maze with alternating open and enclosed arms was investigated as a model for the study of fear-induced behaviour. As predicted, the anxiolytics diazepam and amylobarbitone increased, and the putative anxiogenics ACTH and picrotoxin decreased the proportion of open arm entries. The alpha 1-adrenoceptor agonists phenylephrine and ST587, and the alpha 2-adrenoceptor antagonists idazoxan, piperoxane, RS-21361 and yohimbine decreased relative open-arm entries, thus resembling the putative anxiogenics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
339
6
38

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 877 publications
(394 citation statements)
references
References 19 publications
11
339
6
38
Order By: Relevance
“…Both the elevated X-maze (Handley and Mithani 1984) and the elevated plus-maze (Pellow et al 1985) consist of two opposed arms enclosed by walls except at the central end. These closed arms are perpendicular to two open arms of equal dimensions, which are devoid of any wall.…”
Section: Elevated Mazesmentioning
confidence: 99%
“…Both the elevated X-maze (Handley and Mithani 1984) and the elevated plus-maze (Pellow et al 1985) consist of two opposed arms enclosed by walls except at the central end. These closed arms are perpendicular to two open arms of equal dimensions, which are devoid of any wall.…”
Section: Elevated Mazesmentioning
confidence: 99%
“…This test derives from the early observation that, in mazes consisting of open and closed alleys, rats consistently show higher levels of exploration in enclosed alleys and, when faced with a choice of alley type, typically avoid those without walls (42). Some 30 years later, this finding led to the first studies on the potential utility of an elevated 'X'-maze as a model of anxiety (43). Using a simple maze configuration, elevated 70 cm above floor level and comprising two open and two enclosed arms (like arms opposing one another), these authors not only confirmed that rats avoid the open arms but also demonstrated that open arm avoidance is reduced by diazepam and enhanced by picrotoxin (an anxiogenic agent).…”
Section: The Elevated Plus-mazementioning
confidence: 99%
“…The elevated plus-maze is a widely used and extensively validated animal model of anxiety based on the natural aversion of rodents for open spaces and on the elevation of the maze (Handley and Mithani, 1984;Pellow et al, 1985).…”
Section: Elevated Plus-mazementioning
confidence: 99%